Does Fidaxomicin reduce Cure and Recurrence rates compared to Vancomycin in Clostridium Difficile Infection patients?: A Systematic Review and Meta-analysis (GAIMS Journal of Medical Sciences, 2022)
IntroductionWe searched the databases to include randomized studies evaluating the effect of fidaxomicin on cure and recurrence rate in Clostridium difficile infection (CDI). Due to its increasing severity and recurrence rates, decrease in cure rates, the Infectious Diseases Society of America (IDSA) published clinical practice guidelines in February 2018 moving away from metronidazole as the first-line treatment for initial CDI and recommending, either oral vancomycin or oral fidaxomicin.Methodology              The outcome was summarized as odds ratios (OR) with a 95% confidence interval (CI). We used fixed effect model and assessed the heterogeneity using I2 test. We performed the meta-analysis using ‘Review manager software version 5.4.1.’ResultsThe odds of recurrence rates were significantly different (P < 0.00001) amongst patients treated with fidaxomicin as compared to vancomycin (OR 0.49 [95% CI: 0.36, 0.65]). Whereas no significant difference (P = 0.14) was found with regard to cure rate in both the study groups (OR 0.80 [95% CI: 0.59, 1.07]).ConclusionAfter treatment with fidaxomicin, the rates of clinical cure were non-inferior to those after treatment with vancomycin. However, fidaxomicin was associated with a significantly reduced recurrence rate of CDI including non–North American Pulsed Field type 1 strains.